Digital Health Paradox: International Policy Perspectives to Address Increased Health Inequalities for People Living With Disabilities - van Kessel, Robin; Hrzic, Rok; O'Nuallain, Ella; Weir, Elizabeth; Wong, Brian Li Han; Anderson, Michael; Baron-Cohen, Simon; Mossialos, Elias (Journal of medical Internet research, 2022)
The COVID-19 pandemic accelerated the uptake of digital health worldwide and highlighted many benefits of these innovations. However, it also stressed the magnitude of inequalities regarding accessing digital health. Using a scoping review, this article explores the potential benefits of digital technologies for the global population, with particular reference to people living with disabilities, using the autism community as a case study. We ultimately explore policies in Sweden, Australia, Canada, Estonia, the United Kingdom, and the United States to learn how policies can lay an inclusive foundation for digital health systems. We conclude that digital health ecosystems should be designed with health equity at the forefront to avoid deepening existing health inequalities. We call for a more sophisticated understanding of digital health literacy to better assess the readiness to adopt digital health innovations. Finally, people living with disabilities should be positioned at the center of digital health policy and innovations to ensure they are not left behind.